Profiling immune-evasion pathways in a Merkel cell carcinoma (MCC) - Ioannis M. Koukourakis; Stella Arelaki; Konstantinos V. Tsihrintzis; Alexandra Tsaroucha (Elsevier, 2021)
This case report presents the results of a pilot immuno-phenotypic evaluation of a MCPyV large T-antigen positive Merkel cell carcinoma (MCC). The overall results show a profound immunological imbalance in the MCC microenvironment. An evident prevalence of T-cell infiltration was accompanied by extensive expression of regulatory T-cell markers, like CD25 and FOXP3. An active PDL1/PD1 immunosuppressive pathway is supported by the immunohistochemical findings. The macrophage inhibitory CD47/SIRPα pathway is up-regulated, although macrophage blockage seems to be mediated by a lymphocyte subpopulation expressing CD47, and not by MCC cells that were negative. The most striking finding was the extensive loss of HLA-class-I, and related β2-microglobulin and TAP-1 molecules expression, which predicts for impaired dendritic activation and cancer cell recognition by cytotoxic T-cells. A subset of infiltrating lymphocytes also overexpresses arginase and ectonucleotidases that further contributes to an immunosuppressive arginine-depleted and adenosine-rich microenvironment.